2021
DOI: 10.1371/journal.pone.0245873
|View full text |Cite|
|
Sign up to set email alerts
|

Parental migration and psychological well-being of left-behind adolescents in Western Nepal

Abstract: Introduction International migration is increasing rapidly around the world mostly to obtain a job. International migrant workers usually leave their children back in their country of origin, and among family members, adolescents may experience greater psychological distress from parental separation. However, limited evidence is available on the relationship between parental international migration and psychological well-being of left-behind adolescents. Nepal has a relatively higher and increasing number of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…It indicates that close friendship support strongly contributes to the resilience of adolescents through the provision of social support and active engagement. Furthermore, studies of left‐behind adolescents in China and Nepal have found that school support and friendship quality are important resources for preventing psychosocial problems in left‐behind adolescents due to a lack of family support (Kharel et al, 2021; Zhang & Wang, 2021). However, our study did not find friendship quality directly reduced the risk of later depressive and anxious symptoms but could reduce it by enhancing resilience.…”
Section: Discussionmentioning
confidence: 99%
“…It indicates that close friendship support strongly contributes to the resilience of adolescents through the provision of social support and active engagement. Furthermore, studies of left‐behind adolescents in China and Nepal have found that school support and friendship quality are important resources for preventing psychosocial problems in left‐behind adolescents due to a lack of family support (Kharel et al, 2021; Zhang & Wang, 2021). However, our study did not find friendship quality directly reduced the risk of later depressive and anxious symptoms but could reduce it by enhancing resilience.…”
Section: Discussionmentioning
confidence: 99%
“…The SDQ is a standardized and validated self-administered form that screens for mental health struggles among children ages 4–16 years over the previous 6 months. As a newer instrument, it has not been validated for the Indian or Nepali contexts; however, it has been used by several studies in India for its global scoring system and brevity and has been shown to have acceptable reliability in one study in western Nepal, with a Cronbach's alpha of 0.69 ( 33 , 34 ). Twenty-five items are rated on a 3-point scale (0–2), with 0 = not true and 2 = certainly true, with 5 items reverse scored.…”
Section: Methodsmentioning
confidence: 99%
“…Positive outcomes are found in relation to factors like cultural context, quality of caregiving arrangements, gender of the migrating parent, gender and age of the left-behind child, quality and quantity of communication with children, stability of the parental relationship and remittance driven improvements in living conditions of the child. Research from Nepal on the relationship between parental migration and psychological wellbeing of children suggests that adolescents with an international migrant parent had better psychological outcomes than those living with both parents (Kharel et al, 2021). In Ghana and Nigeria, evidence shows no significant difference in psychological health of children when parents migrate abroad as compared to children of non-migrants (Mazzucato et al, 2015;Mazzucato and Cebotari, 2017).…”
Section: Parental Migration and Psychological Health Of Childrenmentioning
confidence: 99%
“…In cultures like Ghana where child fostering is the prevalent practice, this disruption can be caused indirectly by migration potentially disrupting the primary parental relationship and leading to divorce (Caarls, 2015;Poeze, 2018). Absence of the parent(s) can impact the child directly because of deprivation and indirectly because of the transformation of the physical and psychological environment of the child, resulting in problematic coping mechanisms, as chronicled in a number of studies (White et al, 2003;Parreñas 2005;Dreby, 2010;Graham and Jordan, 2011;Mazzucato & Cebotari, 2017;Kharel, et al, 2021). Furthermore, the nascent stages of cognitive development in younger years are characterised by limited capacity for abstraction leading to confusion in the younger child's mind about the reasons for the parents' absence (Piaget, 1964).…”
Section: Parental Migration and Psychological Health Of Childrenmentioning
confidence: 99%